If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(5x-3)-8=10+4x
We move all terms to the left:
2(5x-3)-8-(10+4x)=0
We add all the numbers together, and all the variables
2(5x-3)-(4x+10)-8=0
We multiply parentheses
10x-(4x+10)-6-8=0
We get rid of parentheses
10x-4x-10-6-8=0
We add all the numbers together, and all the variables
6x-24=0
We move all terms containing x to the left, all other terms to the right
6x=24
x=24/6
x=4
| 4x+-5=7 | | 24x-2+70=180 | | 2/3(x+12)=22 | | 17+7j=67 | | 8x=720 | | 8x–200=144 | | 6x-2+116=180 | | B)(x+4)(x+2)-10=0 | | -z+9=11 | | –10+4k=10−k+10 | | -4x+7x+9=3(x+9) | | 6×(22+6)=w | | 6x-2=116 | | 4m+10+8m=–10+10m | | -1.2x-4+x=8+x-6 | | (3y+99)=(12y+9) | | -(4×+8)=2x-3(2x+3) | | 105x+105=180 | | y-1-0.6y=1.8 | | 3.8x=−19 | | 6=x*4+2 | | -3x-10+6x=-70+7x+16 | | 6=x+6*4 | | 6x-2x+14-2=104 | | 1.5x+2.5x=20 | | 18=30-4p | | 3x+2x+4=84 | | -31-4x=-5-5(1 | | 16x-5+73=180 | | 3x+5−10x+8=x−8x−16−3 | | 2-7b=79 | | -6(-d-12)=6d+15 |